A modified Delphi method to create a scoring system for assessing team performance during maternal cardiopulmonary arrest. (August 2015) - Banayan, Jennifer; Blood, Angela; Park, Yoon Soo; Shahul, Sajid; Scavone, Barbara M.
<x xml:space="preserve">Abstract</x> Background: Maternal cardiopulmonary arrest is a rare but often fatal emergency. The authors used a modified Delphi method to create a checklist of tasks for practitioners. Methods: Within each round, experts ranked tasks on a scale from zero through five. Consensus was defined a priori as 80% exact agreement. Results: Three rounds were required to achieve consensus resulting in a checklist of 45 tasks. Round One results revealed five tasks, Round Two included 25 tasks, and Round Three resulted in 29 tasks with 80% exact agreement. Conclusions: The modified Delphi method resulted in a weighted scoring system that can be used to objectively assess team performance.